Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. PLN (Persero) Kp Gebe Di Kec. Pulau Gebe Kab. Halmahera Tengah - Safi, Fadila; Djaelani, Abdul Kodir; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the influence of style leadership and work motivation on employee perfomance at PT.PLN (Persero) KP GEBE in kec. Gebe island kab. Central Halmahera. Deep sample this research is all employees of PT.PLN (Persero) KP GEBE totaling 35 employees. Thid data collection method uses the distribution method questionaire. This data analysis technique uses linear regression analysis techniques duplicated wits SPSS tools. The result showed that simultaneously leadership style and work motivation have a significant effect on employees performance and partially leadership style and work motivation significantly influence employee performance. Keywords : Leadership Style, Work Motivation, Employee Performance